Electrolysis phenomena in electrophoresis - Novotný, Tomáš; Gaš, Bohuslav (Electrophoresis, 2020)
We present a new theoretical approach for calculating changes in the physico-chemical properties of BGEs for measurements by CZE due to the electrolysis in electrode vials (vessels). Electrolysis is an inevitable phenomenon in any measurement in CZE. Water electrolysis, which occurs in most measurements, can significantly alter the composition of the BGE in electrode vials and in the separation capillary and has a negative influence on the robustness and quality of separations. The ability to predict changes in the composition of the BGE is important for evaluation of the suitability of the BGEs for repeating electrophoretic runs. We compared theoretically calculated changes in the physico-chemical properties (pH, conductivity) with those measured using pH-microelectrode and contactless conductivity detection of the BGE after the electrophoretic run. We confirmed the validity of our theoretical approach with a common BGE composed of acid-base pair, where one constituent is fully dissociated while the second constituent is dissociated by only half, and with Good's buffer. As predicted by theoretical approach, the changes in the physico-chemical properties of the Good's buffer after the electrophoretic run were several times lower than in the case of a common BGE composed of a weak acid - strong base pair.
Keywords: koncentrace vodíkových iontů; elektroforéza kapilární; elektrolyty; pufry; Capillary zone electrophoresis; elektrická vodivost; Electrolytes; Contactless conductivity detection; Hydrogen-Ion Concentration; Electrolysis; Buffers; Electrophoresis, Capillary; Electrodes; elektrolýza; Electric Conductivity; Background electrolyte; elektrody